Targeted Yield based Integrated Nutrient Management of Cabbage in Torripsamment - Yadav, S.R.; Meena, B.S.; Choudhari, Anirudh; Kumar, Sunil (Annals of Arid Zone, 2022)
Soil test crop response correlation studies were conducted to formulate the fertilizer adjustment equations for cabbage (Pusa drum head) under integrated plant nutrition system in Torripsamment during rabi, 2013-14 following Ramamoorthy’s inductive-cum-targeted yield approach. The nutrient requirement for producing one quintal fruit yield of cabbage was 0.31, 0.11 and 0.68 kg of N, P2O5 and K2O, respectively. The per cent contribution from soil and fertilizer nutrients were found to be 19.90 and 17.70 for nitrogen, 31.11 and 11.93 for phosphorus and 30.13 and 53.50 for potassium, respectively. The per cent organic nutrient contribution of FYM was 22.79 for nitrogen, 12.45 for phosphorus and 27.19 for potassium. As per the IPNS based fertilizer prescription equation, for obtaining 20 t ha-1 yield of cabbage on an Torripsammant considering the average soil test values of 100, 30 and 190 kg ha-1 of available N, P2O5 and K2O, respectively the requirement of fertilizer nutrients will be 71.0, 52.1 and 96.5 kg ha-1 of N, P2O5 and K2O, respectively along with 20 t FYM ha-1